LITERATURE REVIEW: THE IMPACT OF PROBLEM-BASED LEARNING (PBL) MODEL ON STUDENTS' COLLABORATION SKILLS IN 21ST CENTURY SCIENCE EDUCATION - Oktavia, Sri Wina; Siburian, Jodion; Hakim, M. Arif Rahman (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2024)
The research aims to review the impact of the Problem-Based Learning (PBL) model on students' collaboration skills in science learning through a literature review of various related studies. The method used is a literature review by analyzing several articles that discuss the use of PBL in science learning and its impact on improving students' collaboration skills. The results showed that PBL significantly contributed to the improvement of students' collaborative skills. With the implementation of PBL, students actively participate in solving problems, discussing and working together effectively, which contributes positively to improving their learning outcomes and scientific communication skills. The research also revealed that the success of PBL implementation is strongly influenced by the teacher's role in managing group dynamics and facilitating the learning process. The implication of the study is that PBL can be adopted as an effective learning model in improving students' collaboration skills. Proper implementation and strong teacher support can ensure the success of PBL implementation in improving students' collaborative skills in various learning contexts, especially in science.